IMPROVEMENTS IN PSYCHOSOCIAL FUNCTIONING AND HEALTH‐RELATED QUALITY OF LIFE FOLLOWING EXERCISE AUGMENTATION IN PATIENTS WITH TREATMENT RESPONSE BUT NONREMITTED MAJOR DEPRESSIVE DISORDER: RESULTS FROM THE TREAD STUDY. Issue 9 (10th May 2016) - Greer, Tracy L.; Trombello, Joseph M.; Rethorst, Chad D.; Carmody, Thomas J.; Jha, Manish K.; Liao, Allen; Grannemann, Bruce D.; Chambliss, Heather O.; Church, Timothy S.; Trivedi, Madhukar H.
Abstract : Background: Functional impairments often remain despite symptomatic improvement with antidepressant treatment, supporting the need for novel treatment approaches. The present study examined the extent to which exercise augmentation improved several domains of psychosocial functioning and quality of life (QoL) among depressed participants. Methods: Data were collected from 122 partial responders to antidepressant medication. Participants were randomized to either high‐ (16 kcal/kg of weight/week [KKW]) or low‐dose (4‐KKW) exercise. Participants completed a combination of supervised and home‐based exercise for 12 weeks. The Short‐Form Health Survey, Work and Social Adjustment Scale, Social Adjustment Scale, Quality of Life Enjoyment and Satisfaction Questionnaire, and Satisfaction with Life Scale were collected at 6 and 12 weeks. Participants with data for at least one of the two follow‐up time points ( n = 106) were analyzed using a linear mixed model to assess change from baseline within groups and the difference between groups for each psychosocial outcome measure. All analyses controlled for covariates, including baseline depressive symptomatology. Results: Participants experienced significant improvements in functioning across tested domains, and generally fell within a healthy range of functioning on all measures at Weeks 6 and 12. Although no differences were found between exercise groups, improvements were observed across a variety of psychosocial and QoL domains, even in the low‐dose exercise group. Conclusions: These findings support exercise augmentation of antidepressant treatment as a viable intervention for treatment‐resistant depression to improve function in addition to symptoms.